The effect of aerobic training with pomegranate juice plasma apolipoproteins in women with type 2 diabetes - احمد عبدی; آسیه عباسی دلویی; مجتبی صالح پور; سیده رقیه فاطمی; سارا ایمن طلب فومنی (Shahid Beheshti University, 2016)
Purpose: Type II diabetes is caused Dyslipidemia. Plasma apolipoproteins are better predictor of cardiovascular diseasethan the traditional lipoproteins. The purpose of this study was to evaluate the effect of aerobic training with pomegranatejuice plasma apolipoproteins in women with type 2 diabetes. Methods: These women were from the county of Babol andwere introduced by the Diabetes Association of this county. 33 women selected and randomly divided into four groups(control, pomegranate juice, training and pomegranate juice-training). Training group's program consisted of 6 weeks ofaerobic exercise training program three sessions a week (Time from 25 minutes to 45 minutes and 60 to 75 % of reservedheart rate). Control- pomegranate juice and pomegranate juice-training were fed 150 ml of pomegranate juice for sixweeks. Two days before and after the training period, blood samples were taken from their brachial veins in afasting state (12 hours prior to the test) in a sitting position. The data was analyzed used of t-independent andANOVA at significance level of P<0.05. Results: the Result showed that significant increase APOA-1, significantdecrease APOB in control- pomegranate juice and pomegranate juice-training and the ratio of APO-B/APOA-1 in all threegroups had a significant decrease. Conclusions: According to the findings of research, it seems aerobic training;pomegranate juice and combination of these can have a beneficial effect in women with type II diabetes and recommendedto the group.